Extracellular Matrix - Leach, Jennie B.; Powell, Elizabeth M.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana Press, 2015)
This volume provides comprehensive procedures for analyzing the extracellular matrix in native, injured, and engineered neural tissues. Divided into four parts, each focusing on different aspects of the extracellular matrix and the nervous system, Extracellular Matrix covers methods to analyze native tissue, in vitro models for investigating cell-extracellular matrix interactions in a variety of contexts, protocols to investigate the role of the extracellular matrix in nervous system injury, degeneration, and regeneration, as well as therapeutics and engineered systems. Each chapter is written by leading experts and presents established protocols in a concise format, encompassing current technologies as well as methods developed over years of research. Beginning with an introduction to the method, chapters continue with a listing of the materials and equipment, step-by-step protocols, and a Notes section with troubleshooting tips, supplemental details and alternative approaches, as well as a list of references for further information. As part of the practical and convenient Neuromethods series, Extracellular Matrix serves as an invaluable aid for researchers studying this vital area of neuroscience.
Immunohistochemical Characterization of Brain Neural and Vascular Basement Membranes -- The Use of Synaptic Basal Lamina and Its Components to Identify Sites of Recent Morphological Alterations at Mammalian Neuromuscular Junctions -- Perineuronal Nets: A Special Structure in the Central Nervous System Extracellular Matrix -- Isolation of Perinatal Mouse Cerebral Cortical Astrocytes -- Techniques for Examining the Effect of Substratum Bound Proteoglycans on Neurite Outgrowth In Vitro -- High-Throughput Quantitative Assay for Analyzing Neurite Outgrowth on a Uniform Substratum: The Cell-Substratum Assay -- Extracellular Matrix Components as a Substrate for Outgrowing Motoneurons -- Replicating the In Vivo Environment: Organotypic and Submerged Three-Dimensional Culture Methods -- Culturing Neurons, Glia, and Progenitor Cells in Three-Dimensional Hydrogels -- Investigating Cell-ECM Interactions and ECM Synthesis in Three-Dimensional Hydrogels -- Characterization and Analysis of Extracellular Matrix in Malignant Brain Tumors and Their Cellular Derivatives -- Chondroitinase Gene Therapy for Spinal Cord Injury -- Modulation of Neural Stem Cell Expressed Extracellular Matrix (ECM) by Targeting Glycosyltransferases -- Evaluating the Spatial and Temporal Protein Production in Neural Tissue Engineering Constructs In Vitro -- Cultivation and Imaging of Astrocytes on Protein-Coated Fluorescent Topographies Constructed from Aligned PLLA Electrospun Fibers -- Engineered Microdevices to Study and Manipulate Neural Stem Cell Chemotaxis -- Hydrolytically Degradable Polyethylene Glycol (PEG) Hydrogel: Synthesis, Gel Formation, and Characterization.
Keywords: Medicine; Neurosciences; Neurobiology; Biomedicine; Neurosciences; Neurobiology; Electronic books